THE ISSUE OF EDUCATION IN TURKISTAN IN THE TIME OF MAHMUDHOJA BEHBUDI - Raimberdiyeva Gulnora; A. Tukhtanazarov (Ta’lim innovatsiyasi va integratsiyasi, 2024)
This article provides information on the activities of schools in Turkestan in the 20th century, the educational system, the introduction of new schools of Jadids, the activities of Mahmudhoja Behbudi, activities aimed at reforming the school system, and the emergence of the Jadid press.